Serum YKL-40 (Chitinase-3-Like Protein 1) Compared to APRI and FIB-4 in Predicting Liver Fibrosis in Children with Chronic Hepatitis C - Mostafa Mohamed Sira; Hanaa Ahmed El-Araby; Enas Mohamed Ghoneim; Hatem Abdel-Sattar Konsowa; Eman Hosny El-Mwafy; Ibrahim A Elhenawy (Archives of Hepatitis Research - Peertechz Publications, 2016)
Background: Liver fi brosis is a critical factor for the treatment policy and its outcome in chronic hepatitis C virus (HCV) infection. Although liver biopsy represents the gold standard for evaluating fibrosis, it remains an invasive procedure with inherent risks. Thus, it cannot be performed frequently to monitor therapeutic outcomes specially in the pediatric population. For that, developing a non-invasive test that can predict liver fi brosis represents a growing medical need. Objectives: to investigate serum levels of YKL-40 and their relation to liver fi brosis in children with chronic HCV. Methods: Serum YKL-40 was measured by enzyme linked immunosorbent assay in 40 treatmentnaive children with proved chronic HCV and the levels were compared according to different laboratory and histopathological parameters. Liver histopathological changes were assessed using Ishak score and compared with aspartate transaminase-to-platelet ratio (APRI) and fi brosis-4 (FIB-4) indices as simple non-invasive markers of fi brosis. YKL-40 was measured in a group of 27 age- and sex-matched healthy controls. Results: YKL-40 was signifi cantly higher in patients than in controls (23.79±11.59 ng/ml vs. 17.67±5.49 ng/ml; P = 0.038). YKL-40 (r = 0.36, P = 0.022), but not APRI (r = -0.176, P = 0.328) or FIB-4 (r = -0.202, P = 0.259), had a signifi cant direct correlation with fi brosis stage. YKL-40 at a cutoff level of ≥24.82  ng/ml could discriminate patients with signifi cant fi brosis (≥F3 Ishak) with 100% sensitivity and 80%  specifi city. Conclusion: YKL-40 signifi cantly correlated with liver fi brosis and could discriminate those with signifi cant fi brosis with acceptable performance.